Effects of Low‐Intensity Endurance Training on Aerobic Fitness and Risk Factors of Cardiometabolic Health in Working‐Age Adults: A Systematic Review and Meta‐Analysis - Nuuttila, Olli‐Pekka; Matomäki, Pekka; Raitanen, Jani; Sievänen, Harri; Vasankari, Tommi (Wiley, 2026)
There is a lack of meta-analyses focusing on low-intensity endurance training (LIT), including considerations of the lowest effective intensity across different outcomes. This systematic review and meta-analysis examined the effects of LIT on aerobic fitness and cardiometabolic health. Randomized controlled trials involving healthy adults aged 18–65 were included if the training intervention was ≥ 3 weeks, intensity was exclusively below the first lactate/ventilatory threshold (VT1), or ≤ 60% heart rate reserve, or maximum oxygen uptake (VO2max), or ≤ 75% maximum heart rate. Outcome variables were VO2max, VT1, systolic and diastolic blood pressure, plasma/serum low-density, high-density, and total cholesterol, triglycerides, and glucose. Effect sizes (ES) were calculated according to Hedge's g. The subgroup analyses (Q-test) examined the effects of training and background characteristics on outcomes. A total of 50 studies with 824 participants in the intervention groups were included. LIT had a large effect on relative VO2max (ES = 0.94, p < 0.001, I2 = 0.73) and a moderate effect (ES = 0.74, p = 0.003, I2 = 0.57) on VT1 compared with the control group. Small but significant effects (|ES| = 0.29–0.44, p < 0.05, I2 = 0.39–0.79) were observed for other variables, excluding glucose. According to the subgroup analysis, exercise intensity was associated with the adaptations only in VO2max (p = 0.02). LIT improved aerobic fitness and cardiometabolic health, but effects on fitness were more pronounced. Although higher exercise intensity was associated with greater adaptations in VO2max, no minimum intensity for adaptations was detected for most outcomes. Notable heterogeneity in responses was observed, which likely reflects both methodological differences (e.g., intensity prescription) between studies and uncertainty regarding the response magnitude.